2007
DOI: 10.33549/physiolres.931303
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of catilages by a novel approach of blunt impact testing

Abstract: The present article introduces a novel method of characterizing the macromechanical cartilage properties based on dynamic testing. The proposed approach of instrumented impact testing shows the possibility of more detailed investigation of the acting dynamic forces and corresponding deformations within the wide range of strain rates and loads, including the unloading part of stress-strain curves and hysteresis loops. The presented results of the unconfined compression testing of both the native joint cartilage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In the present study we addressed the question of whether the main features of articular impact observed in [6,7] could be qualitatively predicted using a linear viscoelastic theory or the linear biphasic theory. It is to note that the deformations encountered in impact tests should be small enough for the linear theories to apply.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present study we addressed the question of whether the main features of articular impact observed in [6,7] could be qualitatively predicted using a linear viscoelastic theory or the linear biphasic theory. It is to note that the deformations encountered in impact tests should be small enough for the linear theories to apply.…”
Section: Discussionmentioning
confidence: 99%
“…The biphasic theory [10], which models the tissue as a mixture of a solid phase and a fluid phase, has demonstrated very good agreement with experimental results in the creep and stress relaxation tests [11]. The objective of this study was to investigate theoretically whether the main features of articular impact observed in [6,7] could be qualitatively predicted using a linear viscoelastic theory or the linear biphasic theory.…”
mentioning
confidence: 98%
See 3 more Smart Citations